2020
DOI: 10.21203/rs.3.rs-50649/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Behavioral Responses of Javanese Medaka (Oryzias Javanicus) Versus Zebrafish (Danio Rerio) in Open Field Test.

Abstract: Background: Locomotion is integral for animal survivability. However, the understandings of locomotor that lead to exhibition of multiple complex behaviors of fish models in response to an open field environment still remain unresolved. To determine whether two different fish models, Javanese medaka and zebrafish have similar baseline locomotor activity in open field paradigm, an open field test was used. Results: Results showed that Javanese medaka exhibit increased in exploratory activity with lower anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
2
1
0
Order By: Relevance
“…In terms of their differences from the zebrafish, all of the medaka fishes exhibited a relatively lower locomotor activity than the zebrafish most of the time. This result is somewhat similar to a prior study in another species of medaka ( Oryzias javanicus ), which found that the medaka fish were passive compared to the D. rerio who were more active and aggressive [ 43 ]. Moreover, a high thigmotaxis level, a preference of animals towards the periphery of a novel arena and avoiding the center area, during the test was displayed by all of the medaka fish [ 44 ].…”
Section: Discussionsupporting
confidence: 90%
“…In terms of their differences from the zebrafish, all of the medaka fishes exhibited a relatively lower locomotor activity than the zebrafish most of the time. This result is somewhat similar to a prior study in another species of medaka ( Oryzias javanicus ), which found that the medaka fish were passive compared to the D. rerio who were more active and aggressive [ 43 ]. Moreover, a high thigmotaxis level, a preference of animals towards the periphery of a novel arena and avoiding the center area, during the test was displayed by all of the medaka fish [ 44 ].…”
Section: Discussionsupporting
confidence: 90%
“…In terms of their differences from zebrafish, all medaka fishes exhibited a relatively lower locomotor activity than zebrafish most of the time. This result is somewhat similar to a prior study in another species of medaka (O. javanicus), which found that the medaka fish were passive compared to D. rerio that were more active and aggressive [37]. Moreover, a high thigmotaxis level, a preference of animals towards the periphery of a novel arena and avoiding the center area, during the test was displayed by all medaka fish [38].…”
Section: Discussionsupporting
confidence: 90%
“…The open eld test (OFT) was utilized to analyze the swimming behavior and locomotor activity of adult zebra sh as described by Sattaa et al, [29]. The OFT is made up of plexiglass (dimensions 30 m height X 30 cm width X10 cm height) containing 5L of water at 28•C.…”
Section: Open Eld Testmentioning
confidence: 99%